The Role of Financial Attitude in Mediating the Influence of Digital Financial Literacy and Impulsivity on Financial Decision Making of Tech-Savvy Investors in DKI Jakarta - William William; Eka Desy Purnama (Dinasti International Journal of Education Management and Social Science, 2025)
Financial literacy play a pivotal role in the economy and community welfare. In the digital era, the ability to navigate financial technology is crucial for making rational investment decisions. However, a paradox exists in Indonesia where high digital adoption does not necessarily correlate with active or rational financial behavior, often due to psychological factors like impulsivity. This study aims to analyze the influence of Digital Financial Literacy and Impulsivity on Financial Decision Making among tech-savvy investors in DKI Jakarta, with Financial Attitude as a mediating variable. Using a quantitative approach, data were collected from 200 respondents categorized as tech-savvy investors through purposive sampling. The data were analyzed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4 software. The results demonstrate that Digital Financial Literacy has a significant positive effect on Financial Decision Making, while Impulsivity has a significant negative effect. Furthermore, Financial Attitude significantly mediates these relationships; it is positively shaped by Digital Financial Literacy and negatively impacted by Impulsivity. The study concludes that fostering a prudent Financial Attitude is essential for mitigating the adverse effects of Impulsivity in the digital investment landscape. These findings suggest that stakeholders must integrate behavioral interventions alongside technical education.